2013
DOI: 10.1109/tevc.2012.2202241
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Lower Bounds on the Running Time of Evolutionary Algorithms

Abstract: We present a new method for proving lower bounds on the expected running time of evolutionary algorithms. It is based on fitness-level partitions and an additional condition on transition probabilities between fitness levels. The method is versatile, intuitive, elegant, and very powerful. It yields exact or near-exact lower bounds for LO, OneMax, long k-paths, and all functions with a unique optimum. Most lower bounds are very general: they hold for all evolutionary algorithms that only use bit-flip mutation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
148
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(153 citation statements)
references
References 56 publications
5
148
0
Order By: Relevance
“…Most of these works derive upper bounds for a specific EDA on the popular OneMax function, which counts the number of 1s in a bit string and is considered to be one of the easiest functions with a unique optimum [17,20]. The only exceptions are Friedrich et al [10], who look at general properties of EDAs, and Sudholt and Witt [18], who derive lower bounds on OneMax for the aforementioned cGA and iteration-best ACO.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these works derive upper bounds for a specific EDA on the popular OneMax function, which counts the number of 1s in a bit string and is considered to be one of the easiest functions with a unique optimum [17,20]. The only exceptions are Friedrich et al [10], who look at general properties of EDAs, and Sudholt and Witt [18], who derive lower bounds on OneMax for the aforementioned cGA and iteration-best ACO.…”
Section: Introductionmentioning
confidence: 99%
“…This simple technique can sometimes provide tight upper bounds of the expected runtime. Recently in [33], an extension of the method has been shown to be able to derive tight lower bounds, the key idea is to estimate the number of fitness levels being skipped on average.…”
Section: Introductionmentioning
confidence: 99%
“…This statement generalises to the class of all evolutionary algorithms that only use standard bit mutation for variation [33] as well as higher mutation rates and stochastic dominance [37]. On the other hand, He et al [10] showed that the highly deceptive function Trap is the hardest function for the (1+1) EA.…”
Section: Introductionmentioning
confidence: 94%